The association of prosomes with some of the intermediate filament networks of the animal cell [published erratum appears in J Cell Biol 1989 Mar;108(3):following 1175] (The Rockefeller University Press, 1988)
The small RNP complexes of defined morphology and biochemical composition termed prosomes, first isolated from the cytoplasm associated with repressed mRNA (Martins de Sa, C., M.-F. Grossi de Sa, O. Akhayat, F. Broders, and K. Scherrer. J. Mol. Biol. 1986. 187:47- 493), were found also in the nucleus (Grossi de Sa, M.-F., C. Martins de Sa, F. Harper, O. Coux, O. Akhayat, P. Gounon, J. K. Pal, Y. Florentin, and K. Scherrer. 1988. J. Cell Sci. 89:151-165). Immunofluorescence, immunoelectron microscopy, and immunochemical studies using mAbs directed against some of the prosomal proteins of duck erythroblasts indicate that in the cytoplasm of HeLa and PtK cells, prosome antigens are associated with the intermediate filament network of the cytokeratin type.